UNIVERSAL JURISDICTION AND THE PRINCIPLE OF NE BIS IN IDEM - MIHAELA AGHENITEI; ION FLAMÂNZEANU (Challenges of the Knowledge Society)
Universal jurisdiction was defined as “the assertion of jurisdiction to prescribe in the absence of any other accepted jurisdictional nexus at the time of the relevant conduct.” Professor Randall, in his seminal work on universal jurisdiction, opined that the theory of universality “provides every state with jurisdiction over a limitedcategory of offenses generally recognized as of universal concern, regardless of the situs of the offence and the nationalities of the offender and the offended. ”Universal jurisdiction is considered a tool for promoting greater justice, but the rights of the accused must be protected. One of the most important guarantees is the principle of ne bis in idem, which protected persons against multiple prosecutions for the same crime. The main legal consequence of the application of ne bis in idem in most systems is the prohibition and inadmissibility of subsequent prosecutions on the same facts blocking effect).The national ne bis in idem principle is established asan individual right in international human rights legal instruments, such as the International Covenant on Civil and Political Rights of 19 December 1966, in Article 14(7). At the regional level, Article 8(4) of the American Convention of Human Rights (1969) and Article 4 (I) of the Seventh Protocol of the European Convention of Human Rights merit mention. In Europe, the ne bis in idem principle is enshrined in Article 54 of the Convention implementing the Schengen Agreement of 14 June 1985, which prohibits the initiation of a second trial for the same offence when final judgment has been imposed upon a person by a court of a contracting party.